Kaos : Dall'Alfa - All'Omega - Terribile, Grazia; Museo Casabianca, Malo (Malo : Museo Casabianca, 1986)
Andrea, Andrea Rossi, Arienti, Stefano ; Barberis, Maurizio ; Bertinetti, Maurizio ; Bonacorsi, Ivo ; Brand, Brigitte ; Caldarelli, Biagio ; Casciello, Angelo ; Cingolani, Marco ; Corona, Maurizio ; De Braud, ALberto ; De Gennaro, Tullio ; De Luca, Michele ; Di Terlizzi, Piero ; Finotti, Carlo ; Fonticoli, Paola ; Gadaleta, Ignazio ; Gelao, Lello ; Giammaria, Nicola ; Jensen, Birgit ; etc.
Kaos : Dall'Alfa - All'Omega, Museo Casabianca, Malo, Aprile 1986
boek